The Impact of Islamic Banks in Financing MSMEs in Serang City : Dampak Bank Syariah Dalam Pembiayaan Umkm Di Kota Serang - Sutikno, Sutikno; Irwani Abdullah, Nurdianawati (Universitas Serang Raya, 2021)
This study aims to determine the impact of BSM in financing MSMEs in Serang City. The impact of BSM in financing MSMEs in Serang City is currently focused on providing business capital and business assistance. To what extent does Serang Branch BSM play an active role in empowering the community's economy in increasing the business of micro customers by continuing to provide capital financing for entrepreneurs who have prospects and meet the requirements in applying for financing The research method used is qualitative research by collecting data. The results of the study found that the factors that influence BSM in financing MSMEs in Serang City are seen from the types of products that are in demand where people's business loans are used as financing that helps small and medium enterprises in running their business